THE DESIRE FOR SOCIAL DEVELOPMENT AND THE EMERGENCE OF IDEAS OF MODERNISM ON THE TERRITORY OF TURKESTAN - Baxritdin Samiyevich Turdiyev (Web of Journals Publishing, 2024)
This article describes the emergence of freedom-minded Jadids educators as a result of the policy of violence in the social, economic and political spheres after the occupation of Turkestan by Tsarist Russia, as well as the emergence of protests from various strata of peoples.
Keywords: Turkistan Territory, jadids of Turkestan, intellectuals of Turkestan, tsarist Russia, tsarist Russian aggression on Central Asian, Central Asian khanates, colonial policy.